2018
DOI: 10.1111/cas.13880
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics suppress colon tumorigenesis through inhibition of aberrant DNA methylation in an azoxymethane and dextran sulfate sodium colitis model

Abstract: Chronic inflammation is involved in the development of colon cancer by inducing mutations and aberrant DNA methylation in colon epithelial cells. Furthermore, there is growing evidence that colonic microbiota modulates the inflammation response in the host and influences colon tumorigenesis. However, the influence of colonic microbiota on aberrant DNA methylation remains unknown. Here, we show the effect of colonic microbes on DNA methylation and tumorigenicity using a mouse model of human ulcerative colitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
0
17
0
2
Order By: Relevance
“…Conversely, suppression of intestinal C. perfringens and C. difficile inhibits colon carcinogenesis in APC-deficient mice [26]. The mechanisms of carcinogenesis promotion by C. perfringens have been suggested, including increase in promoter DNA methylation [27] and induction of production of inflammatory cytokines such as tumor necrosis factor-α and interleukin-12 [28]. In this study, we attempted to clarify the mechanism of YAP activation by CPE.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, suppression of intestinal C. perfringens and C. difficile inhibits colon carcinogenesis in APC-deficient mice [26]. The mechanisms of carcinogenesis promotion by C. perfringens have been suggested, including increase in promoter DNA methylation [27] and induction of production of inflammatory cytokines such as tumor necrosis factor-α and interleukin-12 [28]. In this study, we attempted to clarify the mechanism of YAP activation by CPE.…”
Section: Discussionmentioning
confidence: 99%
“…Usually administered by gavage or drinking water, antibiotics are commonly used in in vivo models to study the impacts of gut microbiome on cancer or other inflammatory diseases. Indeed, antibiotic-mediated microbiome depletion was reported to attenuate CRC development in various studies [82][83][84], and such protective effect is suggested to be primarily through the elimination of the carcinogenic Bacteroides fragilis [85], as well as bacteria that are associated with mucin degradation [86], inflammation and DNA methylation [87].…”
Section: Depletion Of Deleterious Bacteriamentioning
confidence: 99%
“…In ammation has been regarded as a key factor contributing to IBD-CRC, and might promote cancer development via inducing DNA methylation mutation (11), and antibiotics could prevent colon epithelial cell proliferation by inhibiting DNA methylation and mutation (12). Runt-related transcription factor (RUNX) 3 was reported to loss activity in UC associated cancer (13), which might could be used for predict UC associated CRC.…”
Section: Introductionmentioning
confidence: 99%